Surgical Treatment Outcomes of Unresolved Osgood-Schlatter Disease in Adolescent Athletes - Frederick Mun; William L. Hennrikus (Case Reports in Orthopedics)
The purpose of this case series is to report the outcomes of ossicle excision and tubercleplasty for unresolved Osgood-Schlatter disease that has failed conservative treatment in six adolescent athletes. A retrospective chart review was completed, and data collected include age at onset of symptoms, age at surgery, sex, laterality, mechanism of injury, conservative treatment regimen, radiographic findings, sports played, time to return to sport, length of follow-up, and Lysholm score. Surgery involved an open ossicle excision, tubercleplasty, and repair of the patellar tendon to bone using a suture anchor. Postoperatively, patients were allowed to fully weight-bear in an extension knee brace for 4 weeks and then allowed to gradually resume activity. Four males and 2 females were studied. The right knee was involved in 3 cases and the left knee in 3. The average age at onset of symptoms was 15.8 (range 12-18) and at surgery was 17.3 (range 17-18). Radiographic findings included a large bump in 4 cases, an ossicle in 2, and free fragments at the tendon insertion in 3. Sports played included basketball, football, running, and dancing. All patients returned to sports at an average of 21 weeks and 6 days postsurgery (range 8-56). The average length of follow-up was 14.2 weeks (range 5-27). The average Lysholm score postsurgery was 97.2 (range 94-100). Surgical treatment of unresolved Osgood-Schlatter disease was successful in all patients. No patients reported any postoperative complications or additional surgery. For skeletally mature and symptomatic patients, we recommend removal of the ossicle and adjacent bursae, smoothing the bump, and repairing the patellar tendon to bone.